2019
DOI: 10.3400/avd.oa.19-00005
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Simulation of Pancreaticoduodenal Artery Aneurysm Formation Using an Electronic Circuit Model and a Case Series Analysis

Abstract: Objective : To assess mechanisms underlying aneurysm formation using a simple electronic circuit model. Materials and Methods : We created a simple circuit model connecting the celiac artery (CA) to the superior mesenteric artery via the pancreaticoduodenal arcade. We retrospectively reviewed 12 patients with true pancreaticoduodenal artery aneurysms (PDAAs) who received open or endovascular treatment between 2004 and 2017. We set the resistance of each artery and organ volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The results showed that the preoperative condition (time interval 4-5 sec and 11-12 sec) can be reached with either scenario, with the same clinical postoperative status (time interval 6-7 sec and 13-14 sec). Miyahara et al [20] developed an electric model of PDA aneurysm with CA stenosis and showed that as the CA stenosis progressed, the flow through the anterior and posterior PDA decreased, changed their direction, and then increased drastically. They concluded that this increase in the PDA flow might have contributed to the development of a PDA aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the preoperative condition (time interval 4-5 sec and 11-12 sec) can be reached with either scenario, with the same clinical postoperative status (time interval 6-7 sec and 13-14 sec). Miyahara et al [20] developed an electric model of PDA aneurysm with CA stenosis and showed that as the CA stenosis progressed, the flow through the anterior and posterior PDA decreased, changed their direction, and then increased drastically. They concluded that this increase in the PDA flow might have contributed to the development of a PDA aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…Kazuhiro et al . have studied hemodynamic simulation of PDAA using an electric circuit model 23 . They showed that flow volume of the anterior pancreatoduodenal artery and the posterior pancreatoduodenal artery decreases until the CA stenosis progresses up to 50%; thereafter, it increases to up to three times that of the initial volume with retrograde flow.…”
Section: Discussionmentioning
confidence: 99%
“…However, the nonatherosclerotic, inflammatory, mycotic, or false VAAs have a higher risk of rupture, independent of size 4 . In pseudoaneurysms, it is structural wall stress, rather than hemodynamic stress, that drives the arterial wall to deteriorate and ultimately rupture 23,24 . Tulsyan et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…to a pulsatile reversed flow in the GDA akin to that observed in the CHA. (3) As published earlier by our group, the same principle is applied to perfuse the native liver in auxiliary partial orthotopic liver transplantation, thus providing a real-world proof of concept. (4) As shown in our series, GDA flow is adequate to perfuse grafts irrespective of graft size.…”
mentioning
confidence: 86%